(untitled) (International Journal of Engineering and Computer Science, 2015)
Classification of astronomical data has always been a challenging problem faced by astronomers. Classification if performed by ensemble method gives more accurate results than single classifier. In the present study, model for spectral classification is developed using Salford predictive modeler in context of astronomical objects catalogue SDSS. Random forest ensemble method is used for model development and classification results are analyzed. Experimental results show that the model is beneficial for spectral classification.